2017
DOI: 10.1111/apa.13938
|View full text |Cite
|
Sign up to set email alerts
|

Providing teachers with education on epilepsy increased their willingness to handle acute seizures in children from one to 10 years of age

Abstract: Providing a teaching session on epilepsy increased the teachers' knowledge and willingness to act and reduced obsolete, counterproductive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 25 publications
2
23
0
1
Order By: Relevance
“…The follow up-period after intervention ranged from immediately post intervention 70 to one year follow up 65 . The interventions where described mostly consisted of once-off presentation/workshops.…”
Section: Intervention Studiesmentioning
confidence: 99%
“…The follow up-period after intervention ranged from immediately post intervention 70 to one year follow up 65 . The interventions where described mostly consisted of once-off presentation/workshops.…”
Section: Intervention Studiesmentioning
confidence: 99%
“…This may be related to the teachers' professional training regarding health-care. Dumeier et al demonstrated that education may be useful in improving those issues, and the rate of teachers in their survey who would place something solid in a seizing child's mouth decreased from 13-7% after a 40-minute training session [25]. This shows that training on epilepsy knowledge is very useful.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that training on epilepsy knowledge is very useful. In some countries, including Italy [26], Nigeria [27], and Germany [25,28], teachers have been trained on how to handle epileptic episodes, and the results have indicate that carrying out epilepsy knowledge training has a great effect on improving the appropriateness of teachers' rst-aid measures for seizures and their attitudes towards children with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have explored the extent of knowledge and experiences regarding these issues. These have focussed on teachers (Dumeier et al, 2015;2017a;2017b), parents (Lewis et al, 2010;Bertsche et al, 2013;Spindler et al, 2017), patients (Lewis et al, 2010;Bertsche et al, 2013;Spindler et al, 2017), patients (Lewis et al, 2010;Pauschek et al, 2016;Kadel et al, 2018), or the public (Fong and Hung, 2002;Kartal and Akyıldız, 2016;Jansen et al, 2017). A recent study investigated the educational needs of physicians working in paediatric epileptology with emphasis on neurologists and neuropaediatricians (Murray et al, 2018).…”
mentioning
confidence: 99%